High-dose antidepressants affect near-infrared spectroscopy signals: A retrospective study - Takamiya, Akihiro; Hirano, Jinichi; Ebuchi, Yuki; Ogino, Satoyuki; Shimegi, Kenichi; Emura, Hiroyuki; Yonemori, Kyoko; Shimazawa, Akiko; Miura, Gentaro; Hyodo, Ayako; Hyodo, Sari; Nagai, Tunetaka; et al. (NeuroImage clinical, 2017)
Recent studies have highlighted the clinical usefulness of near-infrared spectroscopy (NIRS) in psychiatry. However, the potential effects of psychotropics on NIRS signals remain unknown. We conducted a systematic chart review of 40 depressed patients who underwent NIRS scans during a verbal fluency task to clarify the relationships between psychotropic dosage and NIRS signals. The dosage of psychotropic medications was calculated using defined daily dose (DDD). We investigated the associations between the DDD of psychotropic medications and oxygenated hemoglobin (oxy-Hb) in single channel levels. Retrospective study design and small sample size are the main limitations. Multiple regression analysis revealed that one channel in the right temporoparietal region had a significant association with antidepressant DDD controlling for age, sex, depression severity, and the DDD of antipsychotics and benzodiazepines. Moreover, high doses of antidepressants had significant effects on NIRS signals compared with low doses, in group comparisons. The dose-dependent impact of antidepressants on NIRS signals should be taken into account when interpreting NIRS data. •Antidepressant dose is negatively correlated with right temporoparietal NIRS signals during a verbal fluency task.•The effects of antidepressants are greater at higher dosage.•The effects of antidepressants should be considered when analyzing NIRS signals.